Risk Factors for Stunting in Children Aged 6-36 Months Among Seaweed Farmers in Coastal Areas - Sulidah, Sulidah; Damayanti, Ana; Elmania, Elmania (Journal of Health and Nutrition Research, 2025)
Stunting constitutes a formidable challenge within public health development, necessitating integrated, cross-sectoral strategies for its effective mitigation. A heightened prevalence of stunting is observed in the coastal regions of Tarakan City. This study was designed to elucidate the determinants of stunting among children aged 6–36 months within seaweed farming communities in Tarakan City to inform the formulation of targeted prevention and control policies. An analytical observational study employing a cross-sectional design was conducted from July to September 2023. The target population comprised 200 mothers engaged in seaweed farming in the coastal areas of Tarakan City with children aged 6–36 months. A purposive sampling method was utilized to recruit a sample of 151 participants. Binary logistic regression analysis revealed that stunting was significantly associated (p<0.05) with several variables. Key maternal determinants included the level of knowledge regarding stunting, household income, and residential sanitation conditions. Child-specific determinants encompassed the history of exclusive breastfeeding, morbidity from infectious diseases, and daily protein intake. In conclusion, the prevalence of stunting among children of seaweed farmers in this coastal setting is multifactorial, with significant determinants originating from both maternal and child-related factors. Although certain variables did not yield statistical significance in this analysis, their established role in pediatric health is undeniable. Therefore, it is recommended that comprehensive public health interventions continue to address all investigated factors, given their scientific foundation for promoting optimal child growth and development